Primary delayed gastric emptying after pylorus-resecting pancreatoduodenectomy: A matched-pair comparison of Roux-en-Y vs. Billroth-II reconstruction - Felix O. Hofmann; Victoria S. Engelstädter; Ughur Aghamaliyev; Mathilda M. Knoblauch; Elise Pretzsch; Maximilian Weniger; Jan G. D'Haese; Bernhard W. Renz; Jens Werner; Matthias Ilmer (Surgery Open Science)
Background: After pylorus-resecting pancreatoduodenectomy (PrPD), delayed gastric emptying (DGE) might partially be attributed to biliary reflux. We investigated whether the incidence of primary DGE is reduced after Roux-en-Y instead of Billroth-II reconstruction. Methods: Patients undergoing PrPD from 2016 to 2019 at a high-volume center were identified. Excluding causes of secondary DGE, we matched patients with Roux-en-Y and Billroth-II reconstruction in a 1:2 ratio and compared primary DGE. Results: In 24 vs. 48 (Roux-en-Y vs. Billroth-II) patients, DGE (grade B/C) incidence (20.8 % vs. 18.8 %; P = 1.000), nasogastric tube requirement (median 2 vs. 2 days; P = 0.844) and time to solid food intake (7 vs. 7 days; P = 0.933) were comparable. Univariable logistic regression showed no association between DGE and Roux-en-Y reconstruction (OR 1.47; P = 0.524), in contrast to age (1.08; P = 0.030) and pancreatic biochemical leak (4.98; P = 0.007). Conclusions: Primary DGE did not differ between Roux-en-Y and Billroth-II reconstruction after PrPD. Instead, age and postoperative pancreatic biochemical leak were associated with higher DGE risk.